(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article presents a linguostatistical analysis of Sidqiy Xondayliqiy’s ghazal with the radif “Menga.” Lexical units expressing independent meaning and those lacking independent meaning are classified according to parts of speech. The study also determines whether the units belong to the native or borrowed lexical layer.